PENINGKATAN PEMAHAMAN MATERI BANGUN RUANG MELALUI PENDEKATAN ETNO-STEAM PADA SISWA KELAS 2 SEKOLAH DASAR - Sri Rahayu; Vicky Dwi Wicaksono; Selviari; Satrio Budiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics teaching that focuses on understanding concepts and passive knowledge transfer hinders the development of students' critical thinking skills. The pretest results for geometry scored only 52, below the minimum mastery criteria (KKM), indicating incomplete learning. The type of research conducted is Classroom Action Research (CAR). The subjects of this study were 27 second-grade students in the 2023/2024 academic year. The procedure followed in this classroom action research, using a spiral reflection system, includes planning, implementation, observation, and reflection. Data collection techniques involved observation and questionnaires, while data analysis used N-Gain. The implementation of Etno-STEAM learning achieved a score of 87% in the first cycle and 80% in the second cycle. The average student learning outcome was 90, with an 81% improvement in academic performance. Student responses to Etno-STEAM learning scored 84.4% and 88.1%. Overall, it is classified as very good. Thus, Etno-STEAM learning can be an effective approach to improving learning outcomes in geometry and enhancing students' creativity.